From "West Leads East" to "West Meets East": Philosophical insights from Asia - Luo, Yadong (2014)
In the aftermath of the global economic crisis, the pursuit of new perspectives and different growth models is imperative. One of the most significant trends of our time is the rise of Asia in the world economy. After centuries of Western economic dominance, China, India, and the rest of the East, alongside emerging economies more broadly, are beginning to challenge the West for positions of global industry leadership and underlying managerial philosophies and perspectives. In this paper, I review some key philosophical insights from Asia that have underpinned the success of many Asian businesses for generations, hoping that it will encourage more efforts conceptually, theoretically, and empirically leading the discourse on fresh new perspectives on business in emerging economies in general, and on Asian management in particular.